(untitled) (Prithvi Academic Journal, 2018)
The article attempts to investigate the problems, challenges and prospects of administrative system of Prithvi Narayan Campus (PNC) that has been functioning under Tribhuvan University. The qualitative data are obtained from the respondents mainly through the focus group discussion and in-depth interviews. Quantitative data were received from the campus administration. The study unveiled that the mismanagement of human resource, duplication of work, and insufficient coordination among departments and between the campus administration and the central office of Tribhuvan University as a major problem. Likewise, as in other sectors of public service delivery, the administrative system is incapable of maintaining good governance, integrity and transparency. In order to maintain quality administration, the concerned authority needs to strengthen the administrative capability of the campus, recruit quality human resource, adopt e-governance and maintain quality information system.